Dye tracer visualization of flow patterns and pathways in glacial sandy till at a boreal forest hillslope - Laine-Kaulio, Hanne; Backnas, Soile; Koivusalo, Harri; Lauren, Ari (Elsevier, 2015)
Dyes are valuable tracers in visualizing flow patterns and pathways in soil. We applied the dye Acid Blue 9 to unsaturated and saturated soil profiles at a boreal forest hillslope consisting of glacial sandy till, and determined the soil physical properties from soil samples. The objective was to characterize preferential flowpaths, investigate their porosity, extent and connectivity, and complement earlier findings on subsurface flow formation at the site. According to the results, preferential flowpaths were formed by roots, erosion related to soil water flow, freezing thawing cycles, and soil fauna. The role of roots and stones in the formation of preferential flowpaths was emphasized. Porosity of preferential flowpaths was 5.1 +/- 1.8%, and they extended to a depth of about 55 cm from the soil surface; the deepest roots reached the same depth. When the soil saturated, individual preferential flowpaths self-organized into continuous and well-connected lateral flow systems along the slope. At the slope shoulder, preferential flow network covering the entire soil profile, as well as preferential flowpaths on the underlying bedrock surface, were considered crucial for runoff generation. In the midslope area, runoff generation was characterized by lateral preferential flow and the transmissivity feedback phenomenon. At the slope foot, preferential flowpaths in soil below the eluvial horizon were the major runoff contributors. A full saturation of the soil profile at the slope is unlikely under natural conditions. However, lateral flow was found to occur also in unsaturated soil.